2014
DOI: 10.1111/cup.12317
|View full text |Cite
|
Sign up to set email alerts
|

The changes in the expression levels of follicular markers in keratoacanthoma depend on the stage: keratoacanthoma is a follicular neoplasm exhibiting infundibular/isthmic differentiation without expression of CK15

Abstract: KA is a follicular neoplasm with infundibular/isthmic (upper segmental region of hair follicles) differentiation. It is considered that early or proliferative stage tumors show keratin-filled invaginations with infundibular differentiation and gradual isthmic differentiation. Well-developed examples of KA generally show isthmic differentiation in the whole lesions. The regressed stage KAs lose the features of this type of follicular differentiation and show epidermal characteristics. No expression of CK15 (clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 48 publications
1
61
0
1
Order By: Relevance
“…Additionally, KA did not express other keratins, including K7, K8, K15, K18, and K19. 9,30,31 The presence of the K1 and K10 pair was in the upper area of the ORS and may be associated with epithelial maturation once it is expressed in terminally differentiating epidermal keratinocytes and infundibular cells, 31,32 and K6 and K16 are observed in hyperproliferative epithelia or the beginning of the ORS differentiation. 31 K14 is frequently present in the proliferative basal layer of stratified epithelia and hair follicle cells, such as ORS and stem cells located at the hair follicle bulge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, KA did not express other keratins, including K7, K8, K15, K18, and K19. 9,30,31 The presence of the K1 and K10 pair was in the upper area of the ORS and may be associated with epithelial maturation once it is expressed in terminally differentiating epidermal keratinocytes and infundibular cells, 31,32 and K6 and K16 are observed in hyperproliferative epithelia or the beginning of the ORS differentiation. 31 K14 is frequently present in the proliferative basal layer of stratified epithelia and hair follicle cells, such as ORS and stem cells located at the hair follicle bulge.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In addition, K19 is usually negative for labial epidermis but positive in the labial mucosa epithelium, 17 and interestingly, it was negative for KA. 9,30,31 In addition to the keratins and ORS markers, our study analyzed markers in the specialized cell layers of the hair follicle. Hair cortex keratin was observed in the cortex and precortex of the hair follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical KA is a symmetrical, crateriform, exo‐endophytic lesion composed of contiguous, dilated, infundibular structures that have a central large keratotic horn and overhanging epithelial lips. Proliferation of large pale pink cells with a glassy appearance (follicular isthmic differentiation) is a common feature in KA that is more prominent in well‐developed lesions . Besides these features of KA, CFV also showed more verrucous features that differed from those of typical KA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed CK15 staining in the outermost layer of the hair bulge of normal human scalp samples, as well as in the proximal isthmus, infundibulum, outermost layer of the sub-bulge, the basal interfollicular epidermis and eccrine glands [59,60,61]. Exploration of the literature data on development of scarring alopecia led us to the understanding that clones C8⁄144B and LHK15 of anti-CK15 antibodies are mostly used [62], and LHK15 antibody, recognized as a marker for bulge epithelial stem cells in humans [63], was selected for this study. Other investigators have shown that bulge cells may serve as frame builders in the follicular construction of a hair [64], and the opinion that loss of stem cells in the bulge area of the hair follicle is the reason for alopecia has been established [7,22,23].…”
Section: Discussionmentioning
confidence: 99%